Plan de comunicación interna para la empresa campos cultivados - Espinoza Salsavilca, Ariana Aylin (2023)
Campos Cultivados is an agro-export company founded in 1997. Currently, it is a benchmark in the export of sustainable agricultural products (ready to eat). However, there is no team feeling within the company. Operational areas feel isolated and poorly integrated with administrative areas and business leaders. This lack of integration affects staff retention and meeting the organization's business goals. Therefore, this Professional Sufficiency Work proposes implementing an internal communication plan with the aim of promoting the integration of different profiles and improving the work environment. Leaders will have the necessary tools to serve as support and promote a better employee experience.